OPA Solver: A web-based software for Ordinal Priority Approach in multiple criteria decision analysis using JavaScript - Mahmoudi, Amin; Sadeghi, Mahsa; Deng, Xiaopeng; Pan, Pengcheng (SoftwareX, 2023)
Multiple criteria decision-making (MCDM) is an effective technique for evaluating and selecting alternative(s) based on a set of criteria/sub-criteria. Most MCDM techniques use cardinal data as input data. However, in real-world situations, decision-makers face difficulties, while providingexact values for comparing alternatives/criteria. While “Ordinal Data” is more tangible and straightforward to use by human. Considering human ability in ordinal thinking and expressing preferences, the Ordinal Priority Approach (OPA) was proposed in 2020 to solve the MCDM problems with the ordinal data as input. In the current study, a novel web-based software is developed using JavaScript to streamline and facilitate solving the OPA model. It (i) supports individual and group decision-making, (ii) calculates the weights of the experts, alternatives, and criteria, and (iii) determines confidence level value and uncertainty in the group decision-making problems to check the quality of the input and result. Promisingly, this software is user-friendly for users, time-efficient, accurate for solving MCDM problems, and practical with significant impacts on the academic and industrial worlds.